2019
DOI: 10.1016/j.envpol.2019.07.093
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of thyroid hormone regulated proteins and gene expression by polychlorinated biphenyls, polybrominated diphenyl ethers and new flame retardants in residents of an e-waste region

Abstract: Polychlorinated biphenyls (PCBs), polybrominated diphenyl ethers (PBDEs) and new flame retardants (NFRs) are known thyroid hormone (TH) disruptors, but their disrupting mechanisms in humans are not completely understood. In this study, we aimed to explore the disrupting mechanisms of the aforementioned chemicals via

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 94 publications
(123 reference statements)
1
28
0
Order By: Relevance
“…PBDE concentrations in serum from e-waste recyclers were 1 to 2 orders of magnitude higher than those in non-recyclers whose PBDE concentrations in serum were frequently below limits of detection (Schecter et al, 2018), indicating high occupational exposure of e-waste recyclers to PBDEs. Similar conclusions have been reached in other studies (Eguchi et al, 2015;Guo et al, 2019b;Liang et al, 2016). For instance, in an e-waste recycling site in Wenling, China and an urban area where no e-waste recycling activities were undertaken, 14 PBDE congeners and DBDPE were determined in serum samples taken from e-waste recyclers, non-occupationally-exposed residents of the e-waste site, and urban residents (Liang et al, 2016).…”
Section: Human Blood and Serumsupporting
confidence: 80%
See 2 more Smart Citations
“…PBDE concentrations in serum from e-waste recyclers were 1 to 2 orders of magnitude higher than those in non-recyclers whose PBDE concentrations in serum were frequently below limits of detection (Schecter et al, 2018), indicating high occupational exposure of e-waste recyclers to PBDEs. Similar conclusions have been reached in other studies (Eguchi et al, 2015;Guo et al, 2019b;Liang et al, 2016). For instance, in an e-waste recycling site in Wenling, China and an urban area where no e-waste recycling activities were undertaken, 14 PBDE congeners and DBDPE were determined in serum samples taken from e-waste recyclers, non-occupationally-exposed residents of the e-waste site, and urban residents (Liang et al, 2016).…”
Section: Human Blood and Serumsupporting
confidence: 80%
“…Moreover, PBDEs and NBFRs are reported thyroid hormone (TH) disruptors (Eguchi et al, 2015;Guo et al, 2019b;Zheng et al, 2017aZheng et al, , 2017b. They have strong binding affinity to thyroidstimulating hormone (TSH), thyroglobulin, thyroxine-binding globulin (TBG), TH receptor α (TRα), and iodothyronine deiodinase I (ID1), and therefore could disrupt TH-regulated proteins and gene expression (Guo et al, 2019b). It is also suggested that PBDEs, NBFRs (e.g., DBDPE, BTBPE, BEH-TBP, etc.…”
Section: Potential Health Risks Originated From Human Internal Exposure To Hfrs and Opfrsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Dio, a partial explanation for the preference of Sec of Cys is the greater Lewis basicity of the selenolate over the thiolate [71]. In peri-chalcogen-substituted naphthyl-based Dio mimics, strong nucleophiles have higher Dio-like activity (i.e., Se,Se > Se,S > S,S), consistent with the preference for selenium over sulfur An ongoing debate on the driving forces for the XB interaction has raged in the literature [42,66,[74][75][76][77][78][79][80][81][82]. Briefly stated, one side describes XB as driven primarily by electrostatics, where the donor interacts with an area of positive electrostatic potential on the distal end of the R-X bond, commonly called the "σ-hole" [68,83,84].…”
Section: Introductionmentioning
confidence: 93%
“…An ongoing debate on the driving forces for the XB interaction has raged in the literature [42,66,[74][75][76][77][78][79][80][81][82]. Briefly stated, one side describes XB as driven primarily by electrostatics, where the donor interacts with an area of positive electrostatic potential on the distal end of the R-X bond, commonly called the "σ-hole" [68,83,84].…”
Section: Introductionmentioning
confidence: 99%